2018
DOI: 10.3892/ol.2018.8987
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M treatment increases the responsiveness toward cisplatin‑based chemoradiotherapy in cervical cancer cells in a STAT3‑dependent manner

Abstract: Abstract. Cervical cancer stage-dependent therapies include surgery, chemotherapy, radiotherapy and chemoradiotherapy. Concurrent cisplatin-based chemoradiotherapy (CCRT) is the standard therapy for locally advanced cervical carcinoma (FIGO>IIB), however therapy resistance in a subset of patients is still a major clinical challenge. The present study aimed to analyze the impact of Oncostatin M (OSM) stimulation on CCRT-induced cell death. The present study used cells derived from cervical squamous cell carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…Therefore, SiHa and HeLa cells were treated with OSM, which efficiently activates STAT3 signaling in cervical cancer cells. 17,31 Although STAT3 Y705 phosphorylation was substantially induced by OSM treatment after 1 h, as expected, 42 E6/ E7 protein levels (Figure 5E) were not appreciably altered in either SiHa or HeLa cells. Further, whereas transcript levels of the wellestablished STAT3 target gene SOCS3 43 were substantially induced by OSM treatment (Figure 5F, left panel), HPV E6/E7 transcripts did not increase under the same treatment conditions (Figure 5F, right panel).…”
Section: Genetic Interference With Stat3 Expression Does Not Affect T...supporting
confidence: 79%
See 1 more Smart Citation
“…Therefore, SiHa and HeLa cells were treated with OSM, which efficiently activates STAT3 signaling in cervical cancer cells. 17,31 Although STAT3 Y705 phosphorylation was substantially induced by OSM treatment after 1 h, as expected, 42 E6/ E7 protein levels (Figure 5E) were not appreciably altered in either SiHa or HeLa cells. Further, whereas transcript levels of the wellestablished STAT3 target gene SOCS3 43 were substantially induced by OSM treatment (Figure 5F, left panel), HPV E6/E7 transcripts did not increase under the same treatment conditions (Figure 5F, right panel).…”
Section: Genetic Interference With Stat3 Expression Does Not Affect T...supporting
confidence: 79%
“…Solvent controls were used at a maximum concentration of 0.1% which did not show any effects on cell growth. Oncostatin M (OSM; GenScript Biotech Corporation) was used as indicated for 1, 3, or 6 h at a concentration of 10 ng/mL 17,31 and was dissolved in H 2 O. STAT3 knockout (KO) cells were generated from parental HeLa and SiHa cells by the CRISPR/Cas9 technology, 32 employing two different STAT3-specific guide RNAs (gRNAs). Single cell STAT3 KO clones SiHa G3 and HeLa F3 were generated using the gRNA sense: 5′-CACCGAAAGTGGTAGAGAATCTCC-3′; antisense: 5′-AAACGGAGAT TCTCTACCACTTTC-3′, while for STAT3 KO clones SiHa G7 and HeLa F7 the gRNA sense: 5′-CACCTGTACAGCACCGGCCGATGC-3′; antisense: 5′-AAACGCATCGGCCGGTGCTGTACA-3′ was utilized.…”
Section: Methodsmentioning
confidence: 99%
“…CCND1 is often overexpressed in tumors, and its expression is positively correlated with activation of the JAK/STAT pathway [ 44 ]. In addition, studies showed the JAK/STAT pathway played a crucial role in cisplatin resistance of CC [ 45 , 46 ]. Furthermore, our qPCR validation revealed that STAT1 was upregulated in SiHa cells overexpressing BRCA1 in our study.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL9/OSM/PD-L1: According to bioinformatics database (Cancer Genome Atlas and Gene Expression Omnibus) analysis which was then confirmed by in vitro and in vivo experiments, PD-L1 expression is upregulated by CXCL9-11 through activation of the STAT/PI3K-Akt pathways [ 39 ]. Interestingly, OSM also binds to the OSM receptor, leading to the recruitment of JAKs and subsequent signal transduction and activation of STAT3 [ 40 ]; thus, we can hypothesize that both CXCL9 and OSM participate in the upregulation of PD-L1 through the STAT activation pathway in COVID-19 patients ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%